A high-performance textile pressure sensor based on carbon black/carbon nanotube-polyurethane coated fabrics with porous structure for monitoring human motion. (December 2022) - Zhu, Hao; Dai, Shengping; Cao, Jie; Bai, Hongyu; Zhong, Yan; Zhang, Zhongqiang; Cheng, Guanggui; Yuan, Ningyi; Ding, Jianning
Abstract: Recently, wearable pressure sensors have increasingly attracted much attention due to their potential applications in human motion detection and personal health monitoring. To date, it is still a challenge to fabricate flexible pressure sensor with both comfort and high performance. In this study, we demonstrate a novel and simple blade-dip-coating method to manufacture an all-textile-based pressure sensor. we fabricated a close-fitting pressure sensor assembled from a porous structured carbon nanotube/carbon black-polyurethane (CNT/CB-PU) coated fabrics and the fabric patterned with conductive nylon fiber interdigitated electrode, which can be used as the sensing layer and the electrode layer, respectively. The assembled pressure sensor without polymer encapsulation shows advantages such as flexibility, washable and air permeability. In addition, the sensor also demonstrates excellent performance, including high sensitivity (8.9 kPa −1 for 0–2.3 kPa; 37.5 kPa −1 for 2.3–10.6 kPa), a short response time (189 ms), and a wide sensing range (up to 10.6 kPa). Owing to the facile integration of the fabric on clothes, the sensor can be easily attached to the human body to detect human physiological signals accurately, such as hand gestures, wrist pulse, elbow bending, and chest movement, which makes the sensor a powerful candidate in human motion detection and disease diagnosis. Furthermore, a 2 × 2 sensor array was fabricated on clothes substrate and used as flexible wearable touch keyboards systems for realizing spatial resolution pressure mapping and wireless signal transmission without sacrifice of comfort. Considering the breathable (close to the pristine fabric) and washable (10 stirring cycles) features, our work may provide a new strategy for the fabrication of wearable electronics and intelligent textiles. Graphical Abstract: ga1